2006
DOI: 10.2337/dc06-0266
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber Intake, Dietary Glycemic Load, and the Risk for Gestational Diabetes Mellitus

Abstract: OBJECTIVE -We aimed to examine whether pregravid dietary fiber consumptions from cereal, fruit, and vegetable sources and dietary glycemic load were related to gestational diabetes mellitus (GDM) risk.RESEARCH DESIGN AND METHODS -This study was a prospective cohort study among 13,110 eligible women in the Nurses' Health Study II. GDM was self-reported and validated by medical record review in a subsample.RESULTS -We documented 758 incident GDM cases during 8 years of follow-up. After adjustment for age, parity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
234
3
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(261 citation statements)
references
References 46 publications
12
234
3
12
Order By: Relevance
“…Other observational studies with small s.d. have not reported significant associations with GI Zhang et al, 2006). Sahyoun et al (2008), who did not find significant associations between GI, GL or development of type II diabetes, also noted that the homogeneity of glycaemic intake values within their Table 3 Comparison of glycaemic intake and other characteristics between subjects who were and who were not classified as insulin resistant a 26.1 ± 4.4 31.7 ± 6.6 o0.01 26.5 ± 4.8 Waist-to-hip ratio 0.80 ± 0.1 0.84 ± 0.0 o0.01 0.80 ± 0.1 HOMA 1.6 ± 0.8 5.4 ± 1.5 o0.01 1.9 ± 1.3…”
Section: Discussionmentioning
confidence: 99%
“…Other observational studies with small s.d. have not reported significant associations with GI Zhang et al, 2006). Sahyoun et al (2008), who did not find significant associations between GI, GL or development of type II diabetes, also noted that the homogeneity of glycaemic intake values within their Table 3 Comparison of glycaemic intake and other characteristics between subjects who were and who were not classified as insulin resistant a 26.1 ± 4.4 31.7 ± 6.6 o0.01 26.5 ± 4.8 Waist-to-hip ratio 0.80 ± 0.1 0.84 ± 0.0 o0.01 0.80 ± 0.1 HOMA 1.6 ± 0.8 5.4 ± 1.5 o0.01 1.9 ± 1.3…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using the NHS-II data reported that greater potato consumption was related to an increased GDM risk [22]. Potential beneficial factors include a prudent diet, characterised by a high intake of fruit, green leafy vegetables, poultry and fish [21], a Mediterranean diet [23], as well as nut [19] and fibre consumption [24]. Findings from the investigation of joint effects of diet and physical activity, cigarette smoking and BMI indicated that more than 45% of GDM cases might have been prevented if women adopted an overall healthy diet and lifestyle and maintained a healthy body weight before pregnancy [25].…”
mentioning
confidence: 99%
“…of proinflammatory cytokines (Cani et al, 2007), causally linked to insulin resistance (Shoelson et al, 2006). Further, higher fibre consumption, by reducing the risk of gestational diabetes mellitus (Zhang et al, 2006) or by facilitating maternal weight control (Howarth et al, 2001), was presupposed to benefit the infant's metabolic programming. These previous data are in agreement with our findings that maternal intake of fat and specific fat-containing food products affected metabolic markers in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…In these demonstrations, low birth weight is the main risk factor, taken to reflect a poor intrauterine nutritional environment. In well-nourished women, again, child birth weight, low or high, and a suboptimal intrauterine environment have been linked to maternal intake of single dietary factors (Godfrey et al, 1996;Mikkelsen et al, 2006;Moses et al, 2006;Zhang et al, 2006). However, a fact not previously properly addressed, but not to be ignored, is that the diet is always a mixture of several nutrients with possible complex interactions.…”
Section: Introductionmentioning
confidence: 99%